B-cell receptor stereotyped subsets and outcome for patients with chronic lymphocytic leukemia in the HOVON 68 trial - Vojdeman F.J.; Pedersen L.B.; Te Raa D.; Juvonen V.; van Norden Y.; Tjønnfjord G.E.; Kimby E.; Itälä-Remes M.; Rosenquist R.; Langerak A.W.; Evers L.M.; Zenz T.; et al. (OAE Publishing Inc., 2025)
Aim: We here assessed the impact of B-cell receptor stereotypy on progression-free survival (PFS) and overall survival in patients from the HOVON 68 trial.
Methods: Based on IGHV mutational analyses from participating centers in Sweden, Norway, Finland, Denmark, Poland, and the Netherlands, B-cell receptor stereotyped subsets were assigned using the ARResT/AssignSubsets software. Analysis for recurrent mutations was performed by next-generation sequencing by a 454-base platform. All other clinical data were extracted from the HOVON database by November 2016.
Results: In total, 178 out of 192 patients with sequences available were technically suitable for analysis. Thirty-eight patients (21%) were assigned to one of the 19 major subsets: Subset #2 (n = 12, 6.7%), Subset #8 (n = 7, 3.9%), Subset #6 (n = 6, 3.4%), and Subset #1 (n = 5, 2.8%). Other subsets found were: Subsets #3, #5, #31, and #64B. By November 2016, a PFS event had occurred for 150 patients (84%) and 79 patients (44%) had died. The median follow-up time for patients still alive was 78.9 months. Patients with UM-IGHV belonging to Subset #2 had significantly longer PFS than UM-IGHV 3-21-utilizing non-Subset #2 patients [UM-IGHV Subset #2 median PFS 61.3 months (n = 8) vs. UM-IGHV 3-21 non-Subset #2 median PFS 22.3 months (n = 6), P = 0.01]. Overall, no significant differences in PFS between groups were found for patients with M-IGHV.
Conclusion: In the HOVON 68 trial. Subset #2 patients had a good treatment outcome comparable to the outcome for non-high-risk patients with chronic lymphocytic leukemia following fludarabine-cyclophosphamide-rituximab-based treatment.